Swedish resource potential from residues and energy crops to enhance biogas generation - Lönnqvist, T.; Silveira, S.; Sanches-Pereira, Alessandro (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
This paper verifies the plausibility of existing assessments of the biogas potential in Sweden and whether a target of 1.1 TWh of biogas for transport, as per defined by Swedish authorities, can be met within the next ten years. We estimate that the Swedish resource potential for biogas generation from residues and energy crops amounts to 8.86 TWh in the midterm, equivalent to around 9% of the current domestic transport energy consumption. A large share of this potential remains unrealized and there is uncertainty regarding the existing resource potential, especially concerning energy crops. Nevertheless, the remaining biogas potential can make an important contribution to meet targets of an increased share of renewables in transport. The study concludes that not only it is possible to meet the increased demand expected for gas in transport until 2020 but the existing potential could justify more ambitious goals than presently set by Swedish authorities. © 2012 Elsevier Ltd.